PENGARUH DESTINATION BRANDING DAN PRODUK WISATA TERHADAP NIAT BERKUNJUNG KEMBALI MELALUI WORD OF MOUTH (STUDI KASUS PADA OBJEK WISATA ALAM GOA KREO SEMARANG) - Ridho Rahman; Naili Farida (Universitas Diponegoro, 2017)
This study aims to determine the effect of Destination Branding and Tourism Products on Visiting Intentions through Word of Mouth in Goa Kreo Attraction Object. This type of research is eksplanatory research, where data collection techniques used are questionnaires, Sample selected amounted to 100 people with accidental sampling and purposive sampling. The respondents are visitors of Goa Kreo Tourism Object who have been to Goa Kreo and know Kreo Goa information from other people. Based on the above, the researcher suggested that the management of Goa Kreo Tourism Object improves the tourism product, which is to increase the direction of the road to Goa Kreo, improve the tourist attraction, improve the facilities and be more active in offering guide to the visitors, and clarify the employee job desk, Tourist visit in Goa Kreo.